2009
DOI: 10.1111/j.1399-6576.2008.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal magnesium, fentanyl, or placebo combined with bupivacaine 0.5% for parturients undergoing elective cesarean delivery

Abstract: In patients undergoing cesarean section with spinal anesthesia, the addition of magnesium sulfate (50 mg) i.t. to 10 mg of spinal bupivacaine (0.5%) did not shorten the onset time of sensory and motor blockade or prolong the duration of spinal anesthesia, as seen with fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
3
58
2
1
Order By: Relevance
“…Surgery was allowed to commence on achieving adequate sensory block height (T [8][9] If SBP was > 20% below baseline or 90 mmHg, intravenous (i.v.) ephedrine, 10 mg, was given repeatedly [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery was allowed to commence on achieving adequate sensory block height (T [8][9] If SBP was > 20% below baseline or 90 mmHg, intravenous (i.v.) ephedrine, 10 mg, was given repeatedly [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated use of magnesium intrathecally and shown to prolong the action of subarachnoid anaesthesia [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used an opioid along with magnesium, which could have contributed to the prolongation of blockade after subarachnoid block [6][7][8][9][10][11][12][13], Magnesium alone with LA in a dose of 50 mg and maximum upto 100 mg has been used in a few studies [14][15][16][17][18][19]. Although the results of adding MgSO 4 50 mg to IT bupivacaine are conflicting, the effect of increasing the dose of additional MgSO 4 has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4)(5)(6) Trials with intrathecal and epidural magnesium administration have shown that magnesium is a valuable adjuvant analgesic, but very few data are available on its analgesic effects in lung resection surgery. (7)(8)(9)(10) The aim of the present study was to assess effects of continuous epidural magnesium infusion during thoracic surgery on intraoperative sufentanil consumption and postoperative analgesic requirements during first 48 hours after surgery.…”
mentioning
confidence: 99%
“…4,5 It is likely that intrathecal magnesium sulphate potentiates spinal anaesthesia by a localized action on spinal nociceptive pathways, explaining the absence of central side-effects after systemic administration of large doses of magnesium. 6 As intrathecal magnesium alone has been shown to induce sensory and motor block. 7 It is expected that magnesium might potentiate the spinal block due to a synergistic interaction between NMDA antagonists and LA (local anaesthetic).…”
Section: Introductionmentioning
confidence: 99%